Advanced content delivery, streaming, and cloud services - Pathan, Mukaddim; Sitaraman, Ramesh Kumar 1964-; Robinson, Dom (John Wiley & Sons, Inc., 2014)
"As the subject area of CDN gains research interest and momentum, it is crucial to stay up-to-date with recent developments of its evolutionary track, as well as the current landscape and roadmap. This book provides performance models, case studies, business analyses, and several other important components, so practicing engineers and academics can use the text as a timely reference. Provides an in-depth look at Cloud-based CDNs Includes CDN and streaming media basics and tutorials. Aimed to instruct systems architects, practitioners, product developers, and researchers. Material is divided into introductory subjects, advanced content, and specialist areas"--
Includes index. - Includes bibliographical references at the end of each chapters and index. - Print version record and CIP data provided by publisher
Keywords: Cloud computing; Computer networks; Computer Communication Networks; Infonuagique; Réseaux d'ordinateurs; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference